Administrative and legal regulation of human protection from domestic violence in Kazakhstan and international practice - Surkova, S.S.; Saktaganova, I.S.; Zoll, F. (Bulletin of the Karaganda University “Law Series”, 2023)
This article examines the main legal powers of the competent authorities for the protection of human rights from domestic violence in the families of the Republic of Kazakhstan and in international law. Also, the legislative practice of the post-Soviet countries is considered. At the same time, in foreign countries there is a well-developed system for resolving issues of human protection from domestic violence. The consequences of domestic violence have a number of negative consequences in the future, which adversely affects social development. Analyzing this aspect, in our opinion, it is necessary to thoroughly investigate international experience in combating domestic violence and use the findings in Kazakhstan practice. An important aspect remains a detailed review of the work of the police, as well as innovations in the legislation provided for in the Address to the People of Kazakhstan from 2019. Also, research data on the current state of domestic violence in Kazakhstan are presented. This article deals with topical issues of the application by the competent authorities of the norms for the protection of human rights in domestic violence, including the example of international practice. The article uses the method of comparative analysis of the norms of legislation in the field of domestic violence. In the conclusion of the article, a number of conclusions are proposed, according to the tasks set.